PUBLIC RELATIONS STRATEGY IN MAINTANING GOOD RELATIONSHIPS WITH EXTERNAL STAKEHOLDERS - Siti Hawa; RR. Roosita Cindrakasih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Good relationships between companies and external stakeholders are important for organizational sustainability, especially in the energi sector with diverse stakeholders. PT PLN Indonesia Power UBP Priok is required to maintain trust, meet expectations, and build harmonious relationships with external stakeholders through effective and sustainable public relations strategies. This study aims to analyze the public relations strategy of PT PLN Indonesia Power UBP Priok in maintaning good relationships with external stakeholders. This research uses Stakeholder Theory by Freeman and Relationship Management Theory by Hon and Grunig as the analytical framework. The research method used is a descriptive qualitative approach with a case study design. Data were obtained through in-depth interviews, observation, and documentation involving internal informants and external stakeholders selected using purposive sampling. Public relations strategy of PT PLN Indonesia Power UBP Priok is implemented through the stages of fact finding, planning, communication and action, and evaluation. Relationships with stakeholders are built through two-way communication, community programs, discussion forums, continous evaluation, trust, commitment, satisfaction, and mutual control. This study concludes that the public relations strategy of PT PLN Indonesia Power UBP Priok has been effectively implemented in maintaning good and sustainable relationships with external stakeholders in the long-term sustainable development perspective.